Morphometry and Carcass Characteristics of Goat Fed with Indigofera (Indigofera suffruticosa Mill.) And Super Napier (Pennisetum purpureum Schumach x Pennisetm Glaucoma L.) - Sabaani, Satra A (International Journal of Membrane Science and Technology, 2023)
The study aimed to ascertain the effects of various Indigofera and Super Napier combinations on goats’ morphometry, carcass, and growth characteristics. The experiment was carried out using a completely randomized design (CRD), with six treatments replicated four times. Several treatments were compared using multiple means using the Tukey HSD test. The final weights of the 100% Super Napier-fed goats, 16.93 kg, 16.68 kg, and 16.57 kg, respectively, show that these goats greatly surpassed their size (3.16 kg, 2.90 kg, and 2.67 kg) after a 60-day experiment. 100% Indigofera also affected the chest circumference (57.20 cm), loin eye area (11.66 cm2), hot carcass weight (6.72 kg), pluck weight (0.68kg), and percentage weight of total trimmable fats (2.02 kg). Goats should be fed a diet of 80% Super Napier and 20% Indigofera. Since the study was only carried out for 60 days, it may be done over a longer time. Higher weights in the GIT contents and a larger chest circumference (cm) were also noted.